Double narratives in the Old Testament: the foundations of method in biblical criticism - Nahkola, Aulikki (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2001)
This text presents a study on the importance of variant forms of Old Testament narratives in prompting the development of the criticism of the Bible. The recognition of the recurrence of stories in variant forms in the Old Testament has been seminal to the birth and development of biblical criticism. The author assesses the role of the "double narrative phenomenon" in the evolution of Old Testament methodology, from its earliest documentary theories to its most recent literary ones, with the help of current literary, folklore and textual studies.